SODIUM FLUORIDE-INDUCED OXIDATIVE STRESS AND HISTOLOGICAL CHANGES IN LIVER OF SWISS ALBINO MICE AND AMELIORATION BY OCIMUM SANCTUM LINN. - Prakash, Bhagwendra; Sabal, Suresh Kumar; Verma, Rajbala; Pj, John; Soni, Inderpal (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study was designed to evaluate hepatotoxicity induced by sodium fluoride (NaF) in Swiss albino mice and amelioration by Ocimum sanctum Linn. Methods: Mice were divided into six groups, Group I received tap water, Group II received low dose of NaF (8 mg/L), Group III high dose of NaF (80 mg/L) in drinking water, Group IV tap water along with 250 mg/kg body weight/day leaf extract of O. sanctum Linn., Group V 8 mg/L NaF in drinking water and 250 mg/kg body weight leaf extract of O. sanctum Linn., and Group VI 80 mg/L NaF in drinking water along with leaf extract of O. sanctum Linn. 250 mg/kg body weight/day for 90 days. On the 91st day, the animals were autopsied and liver tissue samples were taken to assess histopathological changes and oxidative stress by estimating glutathione peroxidase, superoxide dismutase, and catalase. Results: A highly significant decrease in the activity of antioxidant enzymes occurred with the high dose (Group III). Hepatic histopathological architecture exhibited deformities, namely, ballooning, hypertrophy, hepatocellular necrosis, infiltration of mononuclear cells, deformed central vein, sinusoidal dilation, and binucleated cells. Low-dose group (Group II) showed a significant decrease in antioxidant enzyme levels as compared to control group, and histological sections of liver showed dilated sinusoids, infiltration of mononuclear cells, ballooning, and hypertrophy of hepatocytes. Groups IV and V showed no pathological features. Group VI showed less damage to the liver as compared to Group III. Conclusion: The results revealed that the administration of leaf extract of O. sanctum Linn. elicited protection against NaF-induced hepatotoxicity and oxidative stress. It may, therefore, be inferred that fluoride caused hepatotoxicity in Swiss albino mice at the tested dose levels can be ameliorated by O. sanctum Linn.